Investor Perception in Investment Decisions in the Southeast Minahasa Region - Lalamentik, Olivia Josefien; R.M Sinolungan, Alzefin Yolandi; Hercyliana Langie, Jessylistiana (Jurnal Ekuisci, 2024)
Background. Investment is an assessment of a developing area. More and more investors are investing in a region, considering that the region has investment policies that can support economic growth. Purpose. This study aims to determine investor perceptions of Southeast Minahasa's investment decisions. Method. This research is a survey with quantitative research. The population and sample are 80 respondents (full sample). Data collection techniques include observation, interviews, questionnaires, and documentation. Result. Considering that North Minahasa is still a new district, they are trying to continue to increase the level of investment so that it can be appropriately realized, especially in investing in capital goods that can improve local income and make financing assets for the development of Southeast Minahasa Efforts to make Southeast Minahasa a destination for investment cities, are greatly influenced by the perception of influential investors in accessing investment activities. Regions are included in import export activities with favorable stock price considerations, guaranteed national stability, and the prospective existence of banking institutions that play an active role. Conclusion. Investors' perceptions include government policies, economic growth rates, imports and exports, stock prices, national stability, and banking institutions. To increase investment activities, it is necessary to consider the perception of investors who support obtaining opportunities so that Southeast Minahasa becomes the central investment district in the North Sulawesi region.